Development of 1, 3-acetonedicarboxylate-derived glucoside amphiphiles (ACAs) for membrane protein study. Issue 19 (27th April 2022) - Lee, Ho Jin; Ehsan, Muhammad; Zhang, Xiang; Katsube, Satoshi; Munk, Chastine F.; Wang, Haoqing; Ahmed, Waqar; Kumar, Ashwani; Byrne, Bernadette; Loland, Claus J.; Guan, Lan; Liu, Xiangyu; et al.
Abstract : Newly developed amphiphiles, designated ACAs, are not only efficient at extracting G protein-coupled receptors from the membranes, but also conferred enhanced stability to the receptors compared to the gold standards (DDM and LMNG ). Abstract : Detergents are extensively used for membrane protein manipulation. Membrane proteins solubilized in conventional detergents are prone to denaturation and aggregation, rendering downstream characterization of these bio-macromolecules difficult. Although many amphiphiles have been developed to overcome the limited efficacy of conventional detergents for protein stabilization, only a handful of novel detergents have so far proved useful for membrane protein structural studies. Here, we introduce 1, 3-acetonedicarboxylate-derived amphiphiles (ACAs) containing three glucose units and two alkyl chains as head and tail groups, respectively. The ACAs incorporate two different patterns of alkyl chain attachment to the core detergent unit, generating two sets of amphiphiles: ACA-As (asymmetrically alkylated) and ACA-Ss (symmetrically alkylated). The difference in the attachment pattern of the detergent alkyl chains resulted in minor variation in detergent properties such as micelle size, critical micelle concentration, and detergent behaviors toward membrane protein extraction and stabilization. In contrast, the impact of the detergent alkyl chain length on protein stability was marked. The two C11 variants (ACA-AC11 and ACA-SC11 ) were most effective at stabilizing the tested membrane proteins. The current study not only introduces new glucosides as tools for membrane protein study, but also provides detergent structure–property relationships important for future design of novel amphiphiles.